IMPLEMENTATION OF DIVISION SIGNS IN SOME NUMBER SYSTEMS - Kudrat Sapoyevich Jumaniozov; Pulatov Bakhram Nigmatovich (American Journals, 2024)
This article is devoted to signs of division of numbers in some number systems: 3, 4, 5, 6 number systems are divisible by 2, 4, 5, 6 number systems are divided by 3, hexadecimal number system is divided by four.
Keywords: Technique, method, number, figure, number system, division symbols.